Kikuchi-Fujimoto Disease: part of the differential diagnosis of cervical lymphadenopathy in an HIV-positive patient. (July 2015) - Thomson-Glover, R; Lawton, M; Menon, G
A 38-year-old HIV-positive Nigerian woman presented with a three-week history of cervical lymphadenopathy, night sweats, weight loss and fever. Provisional diagnoses of tuberculosis and lymphoma were considered; however, a histological diagnosis of Kikuchi-Fujimoto Disease was reached. This rare benign disease has presenting features that mimic more serious conditions commonly occurring in HIV-positive patients. This case report emphasises the importance of Kikuchi-Fujimoto Disease in the differential diagnosis of cervical lymphadenopathy in HIV-positive patients.